The interplay between autophagy and apoptosis mediates toxicity triggered by synthetic cathinones in human kidney cells - Vaz, I. (2021)
Synthetic cathinones abuse remains a serious public health problem. Kidney injury has been reported in intoxications associated with synthetic cathinones, but the molecular mechanisms involved have not been explored yet. In this study, the potential in vitro nephrotoxic effects of four commonly abused cathinone derivatives, namely pentedrone, 3,4-dimethylmethcatinone (3,4-DMMC), methylone and 3,4-methylenedioxypyrovalerone (MDPV), were assessed in the human kidney HK-2 cell line. All four derivatives elicited cell death in a concentration- and time-dependent manner, in the following order of potency: 3,4-DMMC > MDPV > methylone ≈ pentedrone. 3,4-DMMC and methylone were selected to further elucidate the mechanisms behind synthetic cathinones-induced cell death. Both drugs elicited apoptotic cell death and prompted the formation of acidic vesicular organelles and autophagosomes in HK-2 cells. Moreover, the autophagy inhibitor 3-methyladenine significantly potentiated cell death, indicating that autophagy may serve as a cell survival mechanism that protects renal cells against synthetic cathinones toxicity. Both drugs triggered a rise in reactive oxygen and nitrogen species formation, which was completely prevented by antioxidant treatment with N‑acetyl‑L‑cysteine or ascorbic acid. Importantly, these antioxidant agents significantly aggravated renal cell death induced by cathinone derivatives, most likely due to their autophagy-blocking properties. Taken together, our results support an intricate control of cell survival/death modulated by oxidative stress, apoptosis and autophagy in synthetic cathinones-induced renal injury.